Pengembangan Alat Ukur Inventori Minat Berbasis Spherical Model Of Interest - Alif Syahrul Wahyudi; Asmulyani Asri; Ahmad Ridfah (Jurnal Studia Insania, 2021)
Interest assessment is required to help people explore their interests and liking, especially for people who find it difficult to determine their interest in particular things. Interest assessment is crucial for career exploration. This study aims to develop an inventory for interest assessment based on the Spherical Model of Interest. This study begins with a qualitative process, namely peer review and content validity, that involve five experts. There were 535 participants in this study, consisting of between 16 – 23 years. Quantitative analysis in this study using the JASP program. This study showed that the inventory has excellent and acceptable psychometric properties. The discrimination index of this inventory showed 0,420 – 0,842, the Goodness of fit criteria showed that CFI, TLI, GFI, and RMSEA with good and acceptable. This inventory has a good reliability coefficient of 0,778 – 0,907. This inventory has acceptable psychometric properties to use as an interest assessment tool